The Cambridge handbook of creativity and personality research - Feist, Gregory J. edited; Reiter-Palmon, Roni; Kaufman, James C. (Cambridge handbooks in psychology)
"As individual subjects, creativity and personality have been the focus of much research and many publications. This Cambridge Handbook is the first to bring together these two topics and explores how personality and behavior affects creativity. Contributors from around the globe present cutting-edge research about how personality traits and motives make creative behavior more likely. Many aspects of personality and behavior are examined in the chapters, including genius, emotions, psychopathology, entrepreneurship, and multiculturalism, to analyse the impact of these on creativity. The Cambridge Handbook of Creativity and Personality Research will be the definitive resource for researchers, students and academics who study psychology, personality, and creativity"--